The Clean Energy R&D Strategy for 2°C - Giacomo Marangoni; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper uses an integrated assessment model to quantify the climate R&D investment strategy for a variety of scenarios fully consistent with 2°C. We estimate the total climate R&D investment needs in approximately 1 USD Trillion cumulatively in the period 2010-2030, and 1.6 USD Trillions in the period 2030-2050. Most of the R&D would be carried out in industrialized countries initially, but would be evenly split after 2030. We also assess a `climate R&D deal' in which countries cooperate on innovation in the short term, and find that an R&D agreement slightly underperforms a climate policy based on the extension of the Copenhagen pledges till 2030. Both policies are inferior to full cooperation on mitigation starting in 2020. A global agreement on clean energy innovation beyond 2030 without sufficiently stringent GHG emissions reduction policies is found to be incompatible with 2°C.
Keywords: Q55; Q58; Q48; 330; Clean Energy R&D; Endogenous Technical Change; Climate Policy; 2 Degrees; Durban Action Platform